Molecular Dynamics Simulations of Disordered Materials From Network Glasses to Phase-Change Memory Alloys - Massobrio, Carlo; Du, Jincheng; Bernasconi, Marco; Salmon, Philip S. (Springer Series in Materials Science,, 2015)
This book is a unique reference work in the area of atomic-scale simulation of glasses. For the first time, a highly selected panel of about 20 researchers provides, in a single book, their views, methodologies and applications on the use of molecular dynamics as a tool to describe glassy materials. The book covers a wide range of systems covering "traditional" network glasses, such as chalcogenides and oxides, as well as glasses for applications in the area of phase change materials. The novelty of this work is the interplay between molecular dynamics methods (both at the classical and first-principles level) and the structure of materials for which, quite often, direct experimental structural information is rather scarce or absent. The book features specific examples of how quite subtle features of the structure of glasses can be unraveled by relying on the predictive power of molecular dynamics, used in connection with a realistic description of forces.